Influence of Admission Blood Glucose in Predicting Outcome in Patients With Spontaneous Intracerebral Hematoma - Kongwad, Lakshman I.; Hegde, Ajay; Menon, Girish; Nair, Rajesh (Frontiers in Neurology, 2018)
Background and Aims Hyperglycemia or elevated blood glucose levels have been associated with poor outcomes in patients with ischemic stroke yet control of hyperglycemia has not resulted in good outcomes. The prognostic value of hyperglycemia in spontaneous intracerebral hemorrhage (SICH) is not completely understood. High admission blood glucose (ABG) values have been mitigated by other poor prognosticators like large hematoma volume, intraventricular extension (IVE) of hematoma and poor GCS. The aim of this study was to evaluate the effects of blood glucose levels at admission, on mortality and functional outcomes at discharge and 3 months follow up while considering baseline demographics, radiological and clinical indicators of severity of ICH. Methods: This was a retrospective observational study conducted at a tertiary care. Patients with spontaneous SICH were enrolled from a prospective SICH register maintained at our hospital. Blood glucose values were recorded on admission. Patients with traumatic hematomas, vascular malformations, aneurysms and coagulation abnormalities were excluded from our study. Results A total of 510 patients were included in the study. We dichotomised our cohort into two groups, group A with ABG>160mg/dl and group B with ABG<160mg/dl. Mean blood glucose levels in these two groups were 220.73mg/dl and 124.37mg/dl respectively, with group A having twice the mortality. mRS at discharge and 3 months was better in Group B (p=<0.001) as compared to Group A. Age, GCS, volume of hematoma, ABG, IVE and Hydrocephlaus were significant predictors of mortality and poor outcome on univariate analysis with a p value <0.05. The relationship between ABG and mortality (P=0.249, 95%CI 0.948 to 1.006) and outcome (P=0.538, 95%CI 0.997-1.005) failed to reach statistical significance on multivariate logistic regression. Age, Volume of hematoma and GCS were stronger predictors of mortality and morbidity. Conclusion Admission blood glucose levels was not an independent predictor of mortality in our study when adjusted with age, GCS and hematoma volume. Catastrophic SICH is associated with high ABG, which appears to be a stress response to the severity of bleeding. The effect of high ABG on SICH outcome is probably multifactorial and warrant further research.